2022
DOI: 10.1111/prd.12407
|View full text |Cite
|
Sign up to set email alerts
|

It is all about peri‐implant tissue health

Abstract: Current treatment protocols for the rehabilitation of partially and fully edentulous patients by means of implant-supported restorations are associated with high survival rates, thus representing a predictable alternative to conventional concepts. 1,2 Though survival is a robust outcome to assess the fundamental basis for implant function, it clearly ignores the biological and esthetic status of the surrounding tissues. Similar limitations are also related to the survival assessment of implant-supported prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 48 publications
0
43
0
3
Order By: Relevance
“…This literally means that the clinical absence of erythema, bleeding on probing, inflammation, and suppuration, without considering specific ranges of probing depth or clinical or radiological bone loss, is currently synonymous with peri-implant health. 29 In our opinion, this is much of a periodontal vision of the matter, which detracts from much diagnostic and therapeutic potential to this problem. For some authors, such as Papaspyridakos and colleagues, assessing success should be related to at least four levels of integration related to implant level, peri-implant soft tissue, prosthesis, and patient's subjective evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…This literally means that the clinical absence of erythema, bleeding on probing, inflammation, and suppuration, without considering specific ranges of probing depth or clinical or radiological bone loss, is currently synonymous with peri-implant health. 29 In our opinion, this is much of a periodontal vision of the matter, which detracts from much diagnostic and therapeutic potential to this problem. For some authors, such as Papaspyridakos and colleagues, assessing success should be related to at least four levels of integration related to implant level, peri-implant soft tissue, prosthesis, and patient's subjective evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Recent data has revealed that it presents the most common etiological factor for late implant loss [ 2 ]. Considering the increase in the number of patients undergoing restorative treatment through dental implants and accordingly the increments in the prevalence of peri-implantitis (15–57% at the patient level and 8–28% at the implant level) [ 3 ], it is imperative to apply effective treatment methods to manage these conditions. Otherwise, if peri-implantitis lesions are left untreated, they progress in a non-linear and accelerating manner [ 1 , 4 ].…”
Section: Introductıonmentioning
confidence: 99%
“…Early implant failure is defined as failure prior to the connection of prosthetic restoration [ 1 ] and considered to be low [ 2 ]. Early implant failure is usually attributed to biological factors, surgical trauma, and impaired healing that resulted in a failure to achieve osseointegration [ 3 ].…”
Section: Introductionmentioning
confidence: 99%